Organic Geochemical Characteristics of Ngrayong Formation Polaman Sediment Rock, Northeast Java Basin-Indonesia - Yulfi Zetra; Rafwan Year Perry Burhan; Sulistiyono Sulistiyono; Arizal Firmansyah; Darin Salsabila (Indonesian Journal of Chemistry, 2023)
A study of the sedimentary rocks of the Ngrayong formation has been carried out on five samples from the Polaman outcrop point to determine the potential of coal as a source rock for producing oil and gas through GC-MS analysis. Biomarker analysis shows the presence of n-alkanes (C16-C36) with a bimodal distribution, indicating that the source of organic material in sedimentary rocks comes from bacteria, algae, and vascular plants, which is supported by several parameters such as CPI, OEP, LHCPI, wax index, ACL and AlkTerr values. This dominant source of terrigenous organic matter is also proven by the TAR value, C31/C19, C29/C17 ratio, and several aromatic compounds and their derivatives. Bacterial input as an organic source of allouchtonic sedimentary rocks is also proven by the presence of hopanoid, de-A-lupane biomarkers, and C17/C31 ratio. The oxic deposition environment is indicated by the Pr/Ph ratio. CPI and OEP parameters, C29 bb/ab ratio > 0.15 and C31 22S/(22S+22R) < 1 indicate low maturity of the sediment sample. Several parameters and the presence of biomarkers stated above conclude that Ngrayong coal as a source rock has the potential to produce oil and gas.